EFFECT OF CARAGENAN ON THE QUALITY OF FISH JELLY PRODUCTS OF KAKI NAGA - Resmi Rumenta Siregar; Simson Masengi; Yeni Safitri (Politeknik Kelautan dan Perikanan Dumai, 2023)
Carrageenan has been added to various fish jelly products. Some studies shown that the addition of carrageenan can affect the consumer preferences and the quality of some fish jelly products. So far, there is no study about the consumer preferences and the effect of carrageenan into the chemical composition for fish jelly products made from grouper fish. Therefore this research was conducted to determine the effect of the carrageenan on the chemical composition of fish jelly products and to obtain the best composition of fish and carrageenan. Procedures of making fish jelly products and also sensory analysis are carried out in accordance with Indonesian National Standards (SNI) No. 7759:2013). Sensory test data were analyzed using the kruskal wallis followed by the Least significance Different Test (LSD), while the chemical composition were analyzed using ANOVA (Analysis of Variance). The Kruskal wallis analysis showed that carrageenan has significant effect on appearance of fish jelly products and also has significant effect on the protein and crude fiber content, and no significant effect on the moisture, ash, and fat content. Product with 1% of carrageenan as the the preference of consumer contains 50.96% of water, 1.74% of ash, 10.90% of fat, and 14.59% of protein. It’s composition is in accordance with the Indonesian National Standard (SNI) No. 7759-2013.